Habitat Characteristics Nesting Environment Of Hawksbill Turtle (Eretmochelys imbricata) in the East Yu Island Of Thousand Islands National Park - Nasution, Syafruddin; ', Yulmeirina; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in February until March 2016 at East YuIsland, located in the Thousand Islands National Park. The purpose of this studywas to investigate the characteristics of nesting habitat of hawksbill turtle(Eretmochelys imbricata). The method used in this research is survey method,with measuring directly on the habitat of hawksbill turtle (Eretmochelysimbricata) covering the slope of the beach, texture of sediments, within the nest oftides, temperature of the nest, humidty of the nest, the depth of the nest, fecundity,and the type of vegetation and predators in the nesting habitat. The results showedthat the nesting habitat characteristics vary between nest with each other. Nestingbeach ramps ranged 2,75-4,60Âº with medium sand sediment texture to coarsesand. Hawksbill turtle lay it eggs to the distance between 5-12 meters of theaverage highest tide mark. Temperatures nest ranging between 27-31ÂºC with ahumidity between 15-30%. The dominant vegetation in the area is a nesting plantsbutun (Barringtonia asiatica) whereas the dominant predator was biawak(Varanus salvator).Keywords: Eretmochelys imbricata, Characteristic of nesting environment, EastYu Island, Thousand Islands